(untitled) (Sociologisk Forskning, 2018)
In-between Secular and Religious Expectations: Civil Religion at an Individual Level in Sweden This article responds to recent calls for reconsidering the concept ‘civil religion’ to advance the understanding of how both religious and secular authorities shape individuals’ attitudes towards the religious. ‘Civil religion’ is defined as set of religious symbols and practices that can be studied at an individual level. The analysis utilized representative survey data collected in 2016–2017 in Sweden. Four basic forms of ‘civil religion’ were identified and justified in relation to expectations held by both religious and secular authorities in Sweden over time. The analysis showed that the identified forms of ‘civil religion’ differ in terms of social class, gender and age. The results are taken to raise further research questions about relationships between high socioeconomic status and criticism of religion and about low socioeconomic status and adherence to religious minorities in Sweden. In addition, it is stipulated that a civil religion approach to religious attitudes might shed new light on questions concerning contemporary covenants and shared ideas about the religious.